STUDY OF THE NATURAL SETTLEMENT MODEL OF Xylocopa spp. (Hymenoptera: Anthophoridae) FOR THE ADAPTATION OF SHELTERS IN THE PASSION FRUIT CULTIVATION (Passiflora edulis var. Flavicarpa Degener) - CAICEDO-R., GUADALUPE; VARGAS-G., HÉCTOR; GAVIRIA-M., JAIME (Revista Colombiana de Entomología, 1993)
The natural establishment model of Xylocopa spp. was analyzed with the purpose of obtaining a population increase by the adaptation of dens within yellow passion fruit fields. The observations were made in a 25.5 ha field at the Ingenio Riopaila, located at the municipality of Zarzal (Valle, Colombia), in the tropical rain forest. Observations were made both in the plantation and in areas located within a radio of 2 km; the distribution, wood characteristics, and colonization activity were determined by marking the individuals and the nests. Twenty-five groups of nests were found inside the plantation and 34 within the nearby areas. The horizontal distribution of the nests within the plantation was at random. Outside the plantation, the nest distribution was both at random and contagious. The contagious distribution tends to increase with the establishment time and when a reduction of natural enemies is observed in the vertical distribution. Under natural conditions, there is a variety of woods used for nest-building; softwood was more rapidly colonized than hardwood, but in both cases, functional adaptation for abruption in dens was observed.